Amphiphilic polyurethane capable of realizing post-crosslinking and controllable release of nitric oxide as well as preparation method and application of amphiphilic polyurethane
By introducing post-crosslinkable function and epoxy group side chains into the polyurethane glucose restriction film of the glucose sensor, the problem of the sensor response current is not proportional to the glucose concentration, the mechanical properties and hardness of the membrane are improved, and the shelf life and service life of the product are extended.
Patent Information
- Application Number
- CN202411992246.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-18
AI Technical Summary
The kinetic control of glucose oxidase catalytic reaction of existing glucose sensors results in the sensor response current that cannot be proportional to the glucose concentration, and the glucose-limiting membrane materials of CGM products are low in mechanical properties and hardness, which are easy to degrade, resulting in limited sensor detection range and short service life.
Postcrosslinkable and controlled release of nitric oxide amphiphilic polyurethane material is used. This material introduces double selenium chain segments into the main chain, and imparts the polyurethane postcrosslinking function by introducing side chains containing epoxy groups into the main chain, thereby improving the mechanical strength and hardness of the polyurethane glucose-limiting film and reducing the degradation rate of the double selenium structure.
It improves the mechanical properties and hardness of the polyurethane glucose-limiting film, extends the shelf life of CGM products, enhances the linear response ability of the sensor to glucose concentration, and improves the accuracy and service life of the detection results.
Smart Images

Figure CN119842040A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a post-crosslinkable amphiphilic polyurethane capable of controllably releasing nitric oxide and a preparation method and application thereof, belonging to the technical field of materials for glucose detection. Background Art
[0002] At present, the current-type glucose sensor based on glucose oxidase catalyzing the redox reaction of glucose is limited by the Michaelis kinetic control of the glucose oxidase enzymatic reaction, and the sensor response current cannot be proportional to the glucose concentration, resulting in the extremely limited range of blood glucose concentration that the sensor can detect. Generally, the maximum linear response of the conventional glucose oxidase sensor to glucose concentration is about 2mmol / L, which is lower than the blood glucose level of a normal human body (3.9-6.1 mmol / L), and even lower than the blood glucose level of a diabetic patient, making it difficult to accurately detect the glucose concentration. To overcome this shortcoming, a glucose diffusion limiting membrane layer is usually applied above the sensing layer of the enzyme sensor in the art. This membrane layer is usually some biocompatible polymer material, and the glucose flow rate is regulated based on the pore flow principle or chemical selectivity restriction, so that the glucose concentration actually reacting in the enzyme sensing layer controls the linear interval, thereby improving the glucose linear response interval of the sensor. In other words, the role of this membrane layer is to convert the consumption rate of glucose from the kinetic control of the enzymatic reaction of the enzyme sensing layer to the diffusion control of the membrane layer.
[0003] At present, the glucose diffusion limiting membrane material used in CGM products on the market is a polyurethane containing siloxane oligomers and hydrophilic chain oligomers, or a polymer alloy of polysiloxane polyurethane and hydrophilic polymers. When coating, a polymer solution of a certain viscosity is applied to the electrode surface, and the film is formed in situ after the solvent evaporates. After the CGM electrode is implanted in the human body and works, foreign matter implanted in the human body will activate platelets and adhere to the electrode surface, blocking glucose from penetrating to the electrode surface or consuming glucose, ultimately causing the CGM current signal to drop and the CGM product to fail.
[0004] The current patent 201811558460.0 introduces diselenide segments into the polyurethane main chain by adding diselenide chain extenders. After the CGM electrode coated with the polyurethane film is implanted subcutaneously in the human body, the organic selenium segments can stably catalyze the release of nitric oxide from nitric oxide donors in the blood for a long time, thereby reducing the activation and adhesion of platelets on the electrode surface, improving the biocompatibility of the electrode, and extending the service life of the CGM product.
[0005] However, the polyurethane prepared in this way is a linear polyurethane, which has low mechanical properties and hardness, and the diselendiol structure is easily broken by air or hydrogen peroxide oxidation. Therefore, the polyurethane glucose restriction membrane used in this way will degrade or microphase separate during the storage period or during use. Microphase separation is mainly the movement of polymer chains, and chains with the same polarity aggregate with each other, resulting in changes in glucose permeability during the storage period, thereby causing a decrease in the performance of the CGM product. Summary of the invention
[0006] In order to solve the above problems, a post-crosslinkable amphiphilic polyurethane with controllable release of nitric oxide is provided. The polyurethane material has a diselenide segment in the main chain, and a side chain containing an epoxy group is introduced into the main chain to enable it to have a post-crosslinking function. A crosslinking agent can be added later to prepare a polyurethane glucose restriction membrane, which can improve the mechanical strength and hardness of the amino ester glucose restriction membrane, reduce the degradation rate of the diselenide structure, and increase the shelf life of CGM products.
[0007] According to one aspect of the present application, a post-crosslinkable amphiphilic polyurethane capable of controlling the release of nitric oxide is provided, wherein the main chain of the polyurethane is composed of a hydrophobic segment, a hydrophilic segment, a polydimethylsiloxane segment and -O-(CH2) n -Se-Se-(CH2) n -O- group, wherein n = 1 to 5;
[0008] The main chain is also provided with a side chain containing an epoxy group.
[0009] Optionally, the polyurethane is composed of a hydrophobic segment, a hydrophilic segment, a polydimethylsiloxane segment, -O-(CH2) n -Se-Se-(CH2) n -O- group and a group of formula I,
[0010]
[0011] wherein m=1-10, R1 is selected from methyl and ethyl, R2, R3 and R4 are independently selected from methyl and ethyl, and X is halogen; or
[0012] The polyurethane is composed of a hydrophobic segment, a hydrophilic segment, a polydimethylsiloxane segment,
[0013] -O-(CH2) n -Se-Se-(CH2) n -O- group and the group of formula II,
[0014]
[0015] wherein n=1,5, p=1-5, R5 is selected from H or -CH2X, R6 and R7 R4 are independently selected from methyl, ethyl, propyl, butyl, isobutyl or cyclohexyl, and X is halogen; or
[0016] The polyurethane is composed of a hydrophobic segment, a hydrophilic segment, a polydimethylsiloxane segment,
[0017] -O-(CH2) n -Se-Se-(CH2) n -O- group and a group of formula III,
[0018]
[0019] Preferably, the structural formula of the polyurethane is as shown in Formula IV:
[0020]
[0021] Or the structural formula of the polyurethane is shown in Formula V:
[0022]
[0023] Or the structural formula of the polyurethane is as shown in Formula VI, Formula VII, Formula VIII, Formula IX:
[0024]
[0025]
[0026] In formula IV, formula V, formula VI, formula VII, formula VIII, and formula IX It is a chain segment formed by the reaction of hydrophilic oligomers and hydrophobic oligomers with diisocyanate.
[0027] The values of m, n, and p in the above-mentioned side chains containing epoxy groups determine the distance between the two molecular chains of the polyurethane glucose restriction membrane formed by subsequent cross-linking. Therefore, m is not easy to exceed 10, and n+p is not easy to exceed 10, otherwise the distance between the cross-linking points of the restriction membrane will be too large, which will reduce the effect of the restriction membrane.
[0028] According to another aspect of the present application, a method for preparing a post-crosslinkable amphiphilic polyurethane capable of controlling the release of nitric oxide is provided, comprising the following steps:
[0029] (1) reacting a hydrophilic chain oligomer, a hydrophobic chain oligomer, and a polydimethylsiloxane oligomer with diisocyanate to obtain a precursor;
[0030] (2) reacting the precursor with a diselenide chain extender and a diol chain extender having a functional group A to obtain a chain extension intermediate;
[0031] (3) The chain extension intermediate is mixed with a monomer having a functional group B and an epoxy group, and the functional group A reacts with the functional group B to obtain a post-crosslinkable amphiphilic polyurethane having an epoxy group and capable of controlling the release of nitric oxide.
[0032] The preparation method is simple and easy to operate. The epoxy group is introduced into the side chain of the polyurethane through a diol chain extender with a functional group A and a functional group B, thereby improving the distribution uniformity of the side chain containing the epoxy group on the main chain, thereby improving the cross-linking uniformity of the later polyurethane glucose restriction membrane, being able to evenly reduce the degradation of the diselenide structure, and comprehensively improving the performance of the CMG product.
[0033] Optionally, in step (1), the molar ratio of the hydrophilic chain oligomer, the hydrophobic chain oligomer, the polydimethylsiloxane oligomer and the diisocyanate is (0.411-0.625): (0.103-0.156): (0.027-0.042): 1;
[0034] In step (2), the molar ratio of the sum of the total hydroxyl groups contained in the diselenide chain extender and the diol chain extender with functional group A to the isocyanate groups contained in the diisocyanate is (0.12-0.2:):1;
[0035] The molar ratio of the diselenide diol chain extender to the diol chain extender with functional group A is 1:1.
[0036] In step (3), the molar ratio of the monomer with functional group B and epoxy group to the diol chain extender with functional group A is 1:1.
[0037] Optionally, the diol chain extender with functional group A and the monomer with functional group B and epoxy group are selected from one of the following combinations:
[0038] Ⅰ: The diol chain extender with functional group A is selected from tertiary amine diol chain extenders or diol nitrogen heterocyclic chain extenders, and the monomer with functional group B and epoxy group is selected from monomers with halogen and epoxy group;
[0039] II: The diol chain extender with functional group A is selected from diol chain extenders with halogen, and the monomer with functional group B and epoxy group is selected from monomers with tertiary amine and epoxy group;
[0040] III: The diol chain extender with functional group A is selected from diol chain extenders with disulfide bonds, and the monomer with functional group B and epoxy group is selected from monomers with double bonds and epoxy groups.
[0041] The above three combined reaction modes can all form side chains containing epoxy groups on the main chain, and the reaction conditions are controllable, which is conducive to realizing the functionality of the polyurethane.
[0042] Preferably, the tertiary amine diol chain extender or diol nitrogen heterocyclic chain extender in combination I is selected from at least one of methyldiethanolamine, ethyldiethanolamine, and N,N-bis(2-hydroxyethyl)isonicotinamide, and the monomer with halogen and epoxy group is selected from at least one of epichlorohydrin, epibromohydrin, epifluorohydrin, (iodomethyl)oxirane, 3-iodooxetane, epichlorohydrin, 4-bromo-1,2-oxitane, 2-(chloromethyl)-1,2-oxitane, 3-bromooxitane, 3-ethyl-3-bromomethyloxitane, and 3-(bromomethyl)-2,2-dimethyloxitane;
[0043] The halogen-containing diol chain extender in combination II is selected from at least one of 4-chloro-1,3-butanediol, 4-bromo-1,2-butanediol, dibromoneopentyl glycol, and 1,4-dichloro-2,3-butanediol; the monomer with tertiary amine and epoxy group is selected from at least one of 1,2-epoxy-3-(diethylamino)propane, (oxirane-2-yl)methyl]dipropylamine, butyl(methyl)[(oxirane-2-yl)methyl]amine, N-methyl-N-[(oxirane-2-yl)methyl]cyclohexylamine, and bis(2-methylpropyl)[(oxirane-2-yl)methyl]amine;
[0044] The diol chain extender with a disulfide bond in combination III is selected from at least one of trans-1,2-dithiane-4,5-diol and 3,6-dithia-1,8-octanediol;
[0045] The monomer with a double bond and an epoxy group is selected from at least one of glycidyl methacrylate, allyl glycidyl ether, 2-vinyl oxirane, 2-(1-methylethylene)oxirane, 3,4-epoxy-1-butene, 1,2-epoxy-5-hexene, 1,2-epoxy-4-vinylcyclohexane, 1,2-epoxy-7-octene, and 1,2-epoxy-9-decene.
[0046] In the reaction of the above combination I and combination II, no acid or alkali is added for catalysis, so the ring opening of the epoxy group will not be caused. The two monomer substances generate side chains containing quaternary ammonium salts and epoxy groups. The generated quaternary ammonium salts also have antibacterial properties, so the prepared polyurethane glucose restriction membrane also has antibacterial properties and can reduce inflammation. At the same time, since the reaction of the above combination I and combination II does not add additional acid or alkali substances for catalysis, it can avoid the interference of such substances on the sensor enzyme layer and avoid the inactivation of the enzyme layer, that is, reduce interfering substances and improve the accuracy of the sensor detection results.
[0047] Optionally, the structural formula of the diselenideol chain extender is as shown in Formula VII:
[0048]
[0049] Among them, v=1~5.
[0050] Optionally, the reaction temperature of step (1) is 50-60°C and the reaction time is 6-10h;
[0051] The reaction temperature of step (2) is 50-60°C and the reaction time is 8-12h;
[0052] The reaction temperature of step (3) is 50-60°C and the reaction time is 8-12h;
[0053] Preferably, the reaction temperature of steps (1)-(3) is 55°C, the reaction time of step (1) is 8 hours, and the reaction time of steps (2) and (3) is 10 hours.
[0054] Optionally, the polydimethylsiloxane oligomer is selected from at least one of bis-aminopropyl terminated polydimethylsiloxane and bis-hydroxy terminated polydimethylsiloxane;
[0055] The hydrophilic chain oligomer is selected from at least one of polyethylene glycol, polyetheramine, propylene glycol-ethylene glycol copolymer, and zwitterionic compounds;
[0056] The hydrophobic chain oligomer is selected from at least one of polycarbonate diol, polytetramethylene glycol, and polypropylene glycol;
[0057] The diisocyanate is selected from at least one of diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate and hexamethylene diisocyanate;
[0058] Preferably, the polydimethylsiloxane oligomer is bisaminopropyl terminated polydimethylsiloxane, the hydrophilic chain oligomer is polyetheramine, the hydrophobic chain oligomer is polycarbonate diol, and the diisocyanate is dicyclohexylmethane diisocyanate.
[0059] In the preparation method, the glucose and oxygen permeability of the polyurethane glucose limiting membrane can be regulated by the amount of polydimethylsiloxane oligomer and hydrophilic chain oligomer, and the mechanical strength and hardness of the polyurethane glucose limiting membrane can be regulated by the hard segment content and crosslinking density in the polyurethane, so that the appropriate amount can be selected according to actual needs.
[0060] According to another aspect of the present application, a polyurethane glucose limiting membrane is provided, which is obtained by cross-linking the post-crosslinkable nitric oxide-controllable amphiphilic polyurethane described in any one of the above or the post-crosslinkable nitric oxide-controllable amphiphilic polyurethane prepared by any one of the preparation methods described in the above by adding a cross-linking agent.
[0061] Optionally, the cross-linking agent is selected from at least one of polyetheramine, polyethylene glycol diamine, and polytetramethylene ether diamine;
[0062] Preferably, the cross-linking agent is polyetheramine.
[0063] According to another aspect of the present application, a working electrode for a glucose sensor is provided, wherein the polyurethane glucose limiting membrane described in any one of the above items is provided on the working electrode;
[0064] Preferably, the thickness of the polyurethane glucose limiting membrane is 20-60 μm, preferably 30 μm; and / or
[0065] An enzyme layer is also arranged between the working electrode and the polyurethane glucose limiting membrane, and the enzyme layer includes glucose oxidase;
[0066] More preferably, the thickness of the enzyme layer is 1-10 μm, preferably 3 μm.
[0067] According to yet another aspect of the present application, a glucose sensor is provided, wherein the glucose sensor comprises the working electrode described above.
[0068] The beneficial effects of this application include but are not limited to:
[0069] 1. The post-crosslinkable amphiphilic polyurethane capable of controlled release of nitric oxide of the present application can give the polyurethane a post-crosslinking function by carrying side chains containing epoxy groups. The cross-linking agent is added later to form a cross-linked polyurethane glucose-limiting membrane, which can improve the mechanical strength of the polyurethane glucose-limiting membrane and increase the shelf life of the CGM product.
[0070] 2. The post-crosslinkable nitric oxide-releasing amphiphilic polyurethane of the present application, in the structure formed by post-crosslinking, the crosslinking structure itself and the characteristics of inhibiting the degradation of the diselenide structure work together to stably catalyze the release of nitric oxide from nitric oxide donors in the blood for a long time.
[0071] 3. The polyurethane glucose restriction membrane of the present application uses a cross-linking agent and a post-cross-linkable amphiphilic polyurethane with epoxy groups that can release nitric oxide in a controlled manner under mild reaction conditions and can react at room temperature without a catalyst, so it will not affect the enzyme activity and will not reduce the accuracy of the test results.
[0072] 4. The polyurethane glucose limiting membrane of the present application is prepared by mixing a post-crosslinkable amphiphilic polyurethane capable of controllably releasing nitric oxide with a crosslinking agent, and then coating the electrode surface to form an in-situ film. The process is simple and can be easily industrialized.
[0073] 5. The working electrode for the glucose sensor of the present application has a simple preparation method, and has strong binding ability between the polyurethane glucose limiting membrane and the enzyme layer, and between the polyurethane glucose limiting membrane and the electrode substrate. As the working electrode of the glucose sensor, it has strong linear response ability and accurate detection results, which meets the use requirements of the continuous blood glucose monitoring system. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0075] Figure 1 This is the surface morphology of the polyurethane glucose limiting membrane on the working electrode 1# involved in Example 1 of the present application under a scanning electron microscope.
[0076] Figure 2 This is the cross-sectional morphology of the polyurethane glucose limiting membrane on the working electrode 1# involved in Example 1 of the present application in a dry state under a stereo microscope.
[0077] Figure 3 This is the average rate result of nitric oxide release catalyzed by each polyurethane glucose limiting membrane in Example 1 of the present application.
[0078] Figure 4 This is the time-current curve of the working electrode 1# involved in Example 1 of the present application in glucose solutions of different concentrations. DETAILED DESCRIPTION
[0079] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0080] Unless otherwise specified, the raw materials in the examples and comparative examples of the present application were purchased through commercial channels.
[0081] Unless otherwise specified, the methods used in the examples and comparative examples of the present application are conventional methods in the prior art.
[0082] Example 1
[0083] The present embodiment relates to the preparation of a working electrode for a glucose sensor prepared by using a polyurethane glucose limiting membrane, wherein the polyurethane glucose limiting membrane is obtained by reacting a post-crosslinkable amphiphilic polyurethane capable of controlling the release of nitric oxide and a crosslinking agent. The post-crosslinkable amphiphilic polyurethane capable of controlling the release of nitric oxide in the present embodiment is prepared by combination I: a diol chain extender with a functional group A is selected from a tertiary amine diol chain extender or a diol nitrogen heterocyclic chain extender, and a monomer with a functional group B and an epoxy group is selected from a monomer with a halogen and an epoxy group. The specific preparation is as follows:
[0084] Working electrode 1#
[0085] The preparation of working electrode 1# includes the following steps:
[0086] (1) 40 g of bis-aminopropyl-terminated polydimethylsiloxane oligomer (Mn=10k), 30 g of polycarbonate diol (Mn=2k), 30 g of polyetheramine (Mn=500), 0.2 g of dibutyltin dilaurate, and 600 mL of tetrahydrofuran were added to a 1 L reactor and stirred evenly; the temperature was raised to 55° C., and 30 g of dicyclohexylmethane diisocyanate was added dropwise. After the addition was completed, the reaction was stirred for 8 h to obtain a precursor;
[0087] (2) 4.223 g of chain extender bis(2-hydroxyethyl) diselenide (synthesized by reference, DOI: 10.1002 / adma.201503661) and 2.03 g of methyldiethanolamine were added dropwise to the precursor solution, and the reaction was continued for 10 h to extend the intermediate;
[0088] (3) Then, 1.576 g of epichlorohydrin was added and the reaction was continued for 10 h. The reaction solution was precipitated in deionized water, filtered, and dried to obtain a cross-linkable amphiphilic polyurethane with controllable release of nitric oxide;
[0089] (4) adding 5 g of the cross-linkable amphiphilic polyurethane with controllable nitric oxide release obtained in step (3) to 95 g of tetrahydrofuran, and after fully dissolving, adding 0.05 g of polyetheramine (Mn=600) to dissolve to form a polyurethane glucose restriction membrane solution;
[0090] (5) Glucose oxidase is coated on the electrode surface, and an enzyme layer with a thickness of 3 μm is formed after cross-linking and curing with glutaraldehyde vapor. The polyurethane glucose restriction membrane liquid obtained in step (4) is continuously coated on the enzyme layer by scraping. After the solvent evaporates, a restriction membrane layer with a thickness of 30 μm is formed on the surface of the enzyme layer, thereby obtaining a working electrode 1#.
[0091] like Figure 1 As shown in the figure, the surface morphology of the cross-linked polyurethane glucose limiting membrane on the working electrode 1# was observed by SEM. As can be seen from the figure, the surface structure of the polyurethane glucose limiting membrane on the electrode surface is complete, without holes, cracks, etc., indicating that the physical structure of the polyurethane glucose limiting membrane itself can be guaranteed to be intact during the coating process, which can effectively prevent the enzyme layer from leaking and control the flux of glucose. In addition, Figure 2 As shown, the cross-sectional morphology of the polyurethane restriction membrane layer on the working electrode 1# in the dry state was observed using a stereo microscope. It can be observed that the coated polyurethane glucose restriction membrane can completely wrap the electrode, and the formed thickness is about 30 μm.
[0092] Working electrode 2#
[0093] The preparation steps of working electrode 2# are different from those of working electrode 1# in that: in step (1), 30 g of dicyclohexylmethane diisocyanate is replaced by 25.2 g of dicyclohexylmethane diisocyanate, in step (2), 4.223 g of chain extender bis(2-hydroxyethyl) diselenide is replaced by 2.112 g of bis(2-hydroxyethyl) diselenide, 2.03 g of methyldiethanolamine is replaced by 1.78 g of N,N-bis(2-hydroxyethyl)isonicotinamide, and in step (3), 1.576 g of epichlorohydrin is replaced by 1.40 g of 3-(bromomethyl)-2,2-dimethyloxirane. The remaining steps are the same as those of working electrode 1#.
[0094] Working electrode 3#
[0095] The preparation steps of working electrode 3# are different from those of working electrode 1# in that: in step (1), 30 g of dicyclohexylmethane diisocyanate is replaced by 34.13 g of dicyclohexylmethane diisocyanate, in step (2), 4.223 g of chain extender bis(2-hydroxyethyl) diselenide is replaced by 6.335 g of bis(2-hydroxyethyl) diselenide, 2.03 g of methyldiethanolamine is replaced by 3.05 g of methyldiethanolamine, and in step (3), 1.576 g of epichlorohydrin is replaced by 2.364 g of epichlorohydrin. The remaining steps are the same as those of working electrode 1#.
[0096] Working electrode 4#
[0097] The preparation steps of working electrode 4# are different from those of working electrode 1# in that: in step (1), 30g of dicyclohexylmethane diisocyanate is replaced by 38.35g of dicyclohexylmethane diisocyanate, and in step (2), 4.223g of chain extender bis(2-hydroxyethyl) diselenide is replaced by 5g of bis(2-hydroxyhexyl) diselenide, and the remaining steps are the same as working electrode 1#.
[0098] Working electrode 5#
[0099] The preparation steps of working electrode 5# are different from those of working electrode 1# in that: in step (1), 30g of dicyclohexylmethane diisocyanate is replaced by 29.10g of dicyclohexylmethane diisocyanate, and in step (2), 4.223g of chain extender bis(2-hydroxyethyl) diselenide is replaced by 4.65g of bis(2-hydroxybutyl) diselenide, and the remaining steps are the same as working electrode 1#.
[0100] Working electrode 6#
[0101] The preparation steps of working electrode 6# are different from those of working electrode 1# in that: in step (5), glucose oxidase is coated on the electrode surface to form an enzyme layer with a thickness of 10 μm after solidification, and the polyurethane glucose restriction membrane liquid obtained in step (4) is continued to be scraped on the enzyme layer by scraping. During the evaporation of the solvent, the cross-linking agent cross-links with the polyurethane to form a polyurethane glucose restriction membrane with a thickness of 60 μm on the surface of the enzyme layer. The remaining steps are the same as those of working electrode 1# to obtain working electrode 6#.
[0102] Working electrode 7#
[0103] The preparation steps of working electrode 7# are different from those of working electrode 1# in that: in step (5), glucose oxidase is coated on the electrode surface, and an enzyme layer with a thickness of 1 μm is formed after solidification. The polyurethane glucose restriction membrane liquid obtained in step (4) is then scraped on the enzyme layer. During the evaporation of the solvent, the cross-linking agent cross-links with the polyurethane, forming a polyurethane glucose restriction membrane with a thickness of 20 μm on the surface of the enzyme layer. The remaining steps are the same as those of working electrode 1#, and working electrode 7# is obtained.
[0104] Working electrode D1#
[0105] The preparation steps of working electrode D1# are different from those of working electrode 1# in that: in step (2), 4.223 g of chain extender bis(2-hydroxyethyl) diselenide is replaced with 2.2 g of 1,4-butanediol, and the remaining steps are the same as those of working electrode 1#.
[0106] Working electrode D2#
[0107] The preparation steps of working electrode D2# are different from those of working electrode 1# in that: in step (2), 4.223 g of chain extender bis(2-hydroxyethyl) diselenide is replaced with 2.5 g of diethylene glycol, and the remaining steps are the same as those of working electrode 1#.
[0108] Working electrode D3#
[0109] The preparation steps of working electrode D3# are different from those of working electrode 1# in that: in step (2), 2.03 g of methyldiethanolamine is replaced by 1.53 g of 1,4-butanediol, and step (3) is not reacted. The chain extension intermediate of step (2) is precipitated in deionized water, filtered, and dried to obtain a cross-linkable amphiphilic polyurethane with controllable nitric oxide release. The remaining steps are the same as those of working electrode 1#.
[0110] Test Example 1
[0111] The working electrode prepared in Example 1 was tested, and the hydration time, water absorption rate, glucose diffusion coefficient, diffusion coefficient after continuous testing for 7 days, diffusion coefficient after continuous testing for 15 days, glucose diffusion coefficient after aging for 7 days, and glucose diffusion coefficient after aging for 50 days of its glucose polyurethane limiting membrane were tested respectively. The test results are shown in Table 1, and the test method is as follows:
[0112] Hydration time: Soak the prepared polyurethane glucose limiting membrane in purified water, measure the mass of the polyurethane glucose limiting membrane at regular intervals until the membrane mass does not change, and record the time when the membrane mass does not change, which is the hydration time.
[0113] Water absorption rate: Water absorption rate = (membrane wet mass - membrane dry mass) / membrane dry mass * 100%.
[0114] Diffusion coefficient: The specific steps are as follows:
[0115] (1) Soak the prepared outer membrane in the receiving solution for more than 24 hours until the thickness of the outer membrane no longer changes. Use a micrometer to measure the membrane thickness three times and take the average value. Then soak and clean it with purified water for more than 15 minutes, and dry it for later use;
[0116] (2) Before conducting the penetration test, preheat all test solutions to 32 + 1 °C for later use;
[0117] (3) Open the horizontal transdermal diffusion cell and set the water bath temperature to 32°C. Place the treated outer membrane into each channel of the horizontal transdermal diffusion cell (there are 6 diffusion channels, numbered 1# to 6#), with the smoother surface facing the receiving liquid. Place a stirring bar in the supply chamber and receiving chamber of each channel, select a supply liquid and transfer 5.0 mL to the supply chamber. Add 5.0 mL of receiving liquid to the receiving chamber. Set the magnetic stirring to 250 rpm, record the time, and start the permeation experiment.
[0118] The permeability area is known to be a fixed value A, and the diffusion flux of glucose molecules is J (in mol cm -2 ·s -1 ), the diffusion coefficient is calculated according to the following formula:
[0119]
[0120] Where D is the diffusion coefficient, cm2 / s;
[0121] A is the diffusion permeability area, cm2;
[0122] V is the volume of the solution in the donor chamber and the receiving chamber, mL;
[0123] l is the thickness of the polyurethane glucose restriction membrane, cm;
[0124] △t is the sampling interval, s;
[0125] C10 is the concentration of the supply solution after the previous sampling, mmol / L;
[0126] C20 is the concentration of the receiving solution after the previous sampling, mmol / L;
[0127] C2t is the concentration of the receiving solution after △t time, mmol / L;
[0128] The initial diffusion coefficient refers to the average diffusion coefficient on the first day of the test, the diffusion coefficient after 7 days of continuous testing refers to the average diffusion coefficient on the seventh day of the test, the diffusion coefficient after 15 days of continuous testing refers to the average diffusion coefficient on the seventh day of the test, the glucose diffusion coefficient after 7 days of aging refers to the diffusion coefficient tested after the working electrode has been left at 50°C for seven days, and the glucose diffusion coefficient after 50 days of aging refers to the diffusion coefficient tested after the working electrode has been left at 50°C for fifty days.
[0129] Table 1
[0130]
[0131] It can be seen from Table 1 that the water absorption rate of the polyurethane glucose limiting membrane used in the working electrodes 1#-7# and working electrodes D1#-D3# prepared in this embodiment is between 15% and 20%, and the hydration time is about 12 to 13 hours.
[0132] The diffusion coefficient is related to the hydrophilic content and cross-linking density in the polymer. The diffusion coefficient can be used to characterize whether the internal molecular chains of the polyurethane glucose limiting membrane are degraded. The initial glucose diffusion coefficients of the working electrodes 1#-7# prepared in this embodiment and the glucose diffusion coefficients after aging for 7 days and 50 days can meet the actual use requirements. However, the initial diffusion coefficients and the diffusion coefficients after aging of the working electrodes D1#-D2# are low and cannot meet the actual use requirements. The diffusion coefficients of the working electrode D3# after continuous testing for 7 days and 15 days respectively are due to the continuous generation of hydrogen peroxide, which causes the diselenide bond to break, the cross-linking density to decrease, and the glucose diffusion coefficient to increase, which cannot meet the actual use requirements.
[0133] Figure 3 is the average rate result of the release of nitric oxide catalyzed by the polyurethane involved in this embodiment, according to Figure 3 It can be seen that the introduction of diselendiol chain extenders has been proven to improve the long-term stable release of nitric oxide. After the CGM electrode coated with the polyurethane film is implanted subcutaneously in the human body, the organic selenium chain segments can catalyze the release of nitric oxide from nitric oxide donors in the blood in a long-term and stable manner, thereby reducing the activation and adhesion of platelets on the electrode surface, improving the biocompatibility of the electrode, improving the accuracy of the test, and extending the service life of the CGM product.
[0134] Figure 4 The time-current curves of working electrode 1# in glucose solutions of different concentrations show that, in the range of 0-25 mM glucose concentration, the linear correlation between glucose concentration and current response value is good for working electrode 1#.
[0135] Example 2
[0136] This embodiment relates to the preparation of a working electrode for a glucose sensor prepared by using a polyurethane glucose limiting membrane. The polyurethane glucose limiting membrane is obtained by reacting a post-crosslinkable amphiphilic polyurethane that can controllably release nitric oxide and a crosslinking agent. The post-crosslinkable amphiphilic polyurethane that can controllably release nitric oxide in this embodiment is prepared by II: a diol chain extender with a functional group A is selected from a diol chain extender with a halogen, and a monomer with a functional group B and an epoxy group is selected from a monomer with a tertiary amine and an epoxy group. The specific preparation is as follows:
[0137] Working electrode 11#
[0138] The preparation of working electrode 11# includes the following steps:
[0139] (1) 40 g of bis-aminopropyl-terminated polydimethylsiloxane oligomer (Mn=10k), 30 g of polycarbonate diol (Mn=2k), 30 g of polyetheramine (Mn=500), 0.2 g of dibutyltin dilaurate, and 600 mL of tetrahydrofuran were added to a 1 L reactor and stirred evenly; the temperature was raised to 50° C., and 30 g of dicyclohexylmethane diisocyanate was added dropwise. After the addition was completed, the reaction was stirred for 10 h to obtain a precursor;
[0140] (2) 4.223 g of chain extender bis(2-hydroxyethyl) diselenide and 2.12 g of 4-chloro-1,3-butanediol were added dropwise to the precursor solution, and the reaction was continued for 12 h to extend the intermediate;
[0141] (3) Then, 2.20 g of 1,2-epoxy-3-(diethylamino)propane was added, and the reaction was continued for 12 h. The reaction solution was precipitated in deionized water, filtered, and dried to obtain a cross-linkable amphiphilic polyurethane with controllable release of nitric oxide;
[0142] (4) adding 5 g of the cross-linkable amphiphilic polyurethane with controllable nitric oxide release obtained in step (3) to 95 g of tetrahydrofuran, and after fully dissolving, adding 0.05 g of polyetheramine (Mn=600) to dissolve to form a polyurethane glucose restriction membrane solution;
[0143] (5) Glucose oxidase is coated on the electrode surface, and an enzyme layer with a thickness of 3 μm is formed after cross-linking and curing with glutaraldehyde vapor. The polyurethane glucose restriction membrane liquid obtained in (4) is further coated on the enzyme layer by scraping. After the solvent evaporates, a restriction membrane layer with a thickness of 30 μm is formed on the surface of the enzyme layer, thereby obtaining a working electrode 11#.
[0144] Working electrode 12#
[0145] The difference between working electrode 12# and working electrode 11# is that in step (2), 2.12 g of 4-chloro-1,3-butanediol is replaced by 2.23 g of 1,4-dichloro-2,3-butanediol, and in step (3), 2.20 g of 1,2-epoxy-3-(diethylamino)propane is replaced by 2.88 g of N-methyl-N-[(oxiran-2-yl)methyl]cyclohexylamine, and the remaining steps are the same as working electrode 11#.
[0146] Working electrode 13#
[0147] The difference between working electrode 12# and working electrode 11# is that in step (2), 2.12 g of 4-chloro-1,3-butanediol is replaced by 4.45 g of dibromoneopentyl glycol, and in step (3), 2.20 g of 1,2-epoxy-3-(diethylamino)propane is replaced by 2.43 g of butyl(methyl)[(oxiran-2-yl)methyl]amine, and the remaining steps are the same as working electrode 11#.
[0148] Working electrode 14#
[0149] The difference between working electrode 12# and working electrode 11# is that in step (2), 2.12 g of 4-chloro-1,3-butanediol is replaced by 3.35 g of 6-bromo-1,2-hexanediol, and in step (3), 2.20 g of 1,2-epoxy-3-(diethylamino)propane is replaced by 3.15 g of bis(2-methylpropyl)[(oxiran-2-yl)methyl]amine, and the remaining steps are the same as working electrode 11#.
[0150] Example 3
[0151] The present embodiment relates to the preparation of a working electrode for a glucose sensor prepared by using a polyurethane glucose limiting membrane. The polyurethane glucose limiting membrane is obtained by reacting a post-crosslinkable amphiphilic polyurethane capable of controlling the release of nitric oxide and a crosslinking agent. The post-crosslinkable amphiphilic polyurethane capable of controlling the release of nitric oxide in the present embodiment is prepared by III: a diol chain extender with a functional group A is selected from a diol chain extender with a disulfide bond, and a monomer with a functional group B and an epoxy group is selected from a monomer with a double bond and an epoxy group. The specific preparation is as follows:
[0152] Working electrode 21#
[0153] The preparation of working electrode 21# includes the following steps:
[0154] (1) 40 g of bis-aminopropyl-terminated polydimethylsiloxane oligomer (Mn=10k), 30 g of polycarbonate diol (Mn=2k), 30 g of polyetheramine (Mn=500), 0.2 g of dibutyltin dilaurate, and 600 mL of tetrahydrofuran were added to a 1 L reactor and stirred evenly; the temperature was raised to 50° C., and 30 g of dicyclohexylmethane diisocyanate was added dropwise. After the addition was completed, the reaction was stirred for 10 h to obtain a precursor;
[0155] (2) 4.223 g of chain extender bis(2-hydroxyethyl) diselenide and 3.10 g of 3,6-dithia-1,8-octanediol were added dropwise to the precursor solution, and the reaction was continued for 12 h to extend the intermediate;
[0156] (3) The mixture was cooled to room temperature, 5 g of sodium borohydride was added, the mixture was stirred and reacted for 6 h, and then 2.42 g of glycidyl methacrylate was added and the reaction was continued for 12 h. The reaction solution was precipitated in deionized water, filtered, and dried to obtain a cross-linkable amphiphilic polyurethane with controllable release of nitric oxide;
[0157] (4) adding 5 g of the cross-linkable amphiphilic polyurethane with controllable nitric oxide release obtained in step (3) to 95 g of tetrahydrofuran, and after fully dissolving, adding 0.05 g of polyetheramine (Mn=600) to dissolve to form a polyurethane glucose restriction membrane solution;
[0158] (5) Glucose oxidase is coated on the electrode surface, and an enzyme layer with a thickness of 3 μm is formed after cross-linking and curing with glutaraldehyde vapor. The polyurethane glucose restriction membrane liquid obtained in (4) is further coated on the enzyme layer by scraping. After the solvent evaporates, a restriction membrane layer with a thickness of 30 μm is formed on the surface of the enzyme layer, thereby obtaining a working electrode 21#.
[0159] Working electrode 22#
[0160] The difference between working electrode 22# and working electrode 21# is that in step (2), 3.10 g of 3,6-dithia-1,8-octanediol is replaced by 2.59 g of trans-1,2-dithiane-4,5-diol, and in step (3), 2.42 g of glycidyl methacrylate is replaced by 1.94 g of allyl glycidyl ether, and the remaining steps are the same as those of working electrode 21#.
[0161] Test Example 2
[0162] The working electrodes prepared in Example 2 and Example 3 were tested in the same manner as in Test Example 1. The test results are shown in Table 2.
[0163] Table 2
[0164]
[0165] It can be seen from the data in the above table that the electrodes did not show any sensitivity reduction problem after aging, and the glucose diffusion coefficient of the electrodes tested continuously for 15 days did not change significantly. This is because the polyurethane outer membrane of these electrodes is a cross-linked structure, and even if the diselenide bonds are easily broken by hydrogen peroxide oxidation, the polymer segments remain intact and do not degrade.
[0166] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.
Claims
1. A post-crosslinkable amphiphilic polyurethane capable of controlling the release of nitric oxide, characterized in that: The polyurethane comprises a main chain consisting of a hydrophobic segment, a hydrophilic segment, a polydimethylsiloxane segment and -O-(CH2) n -Se-Se-(CH2) n -O- group, wherein n = 1 to 5; The main chain is also provided with a side chain containing an epoxy group.
2. The post-crosslinkable amphiphilic polyurethane capable of controlled release of nitric oxide according to claim 1, characterized in that: The polyurethane consists of a hydrophobic segment, a hydrophilic segment, a polydimethylsiloxane segment, -O-(CH2) n -Se-Se-(CH2) n -O- group and a group of formula I, wherein m=1-10, R1 is selected from methyl and ethyl, R2, R3 and R4 are independently selected from methyl and ethyl, and X is halogen; or The polyurethane consists of a hydrophobic segment, a hydrophilic segment, a polydimethylsiloxane segment, -O-(CH2) n -Se-Se-(CH2) n -O- group and the group of formula II, wherein k=1-5, p=1-5, R5 is selected from H or -CH2X, R6 and R7 R4 are independently selected from methyl, ethyl, propyl, butyl, isobutyl or cyclohexyl, and X is halogen; or The polyurethane consists of a hydrophobic segment, a hydrophilic segment, a polydimethylsiloxane segment, -O-(CH2) n -Se-Se-(CH2) n -O- group and a group of formula III, Preferably, the structural formula of the polyurethane is as shown in Formula IV: Or the structural formula of the polyurethane is shown in Formula V: Or the structural formula of the polyurethane is as shown in Formula VI, Formula VII, Formula VIII, Formula IX: In formula IV, formula V, formula VI, formula VII, formula VIII, and formula IX It is a chain segment formed by the reaction of hydrophilic oligomers and hydrophobic oligomers with diisocyanate.
3. A method for preparing a post-crosslinkable amphiphilic polyurethane capable of controlling the release of nitric oxide, characterized in that: The steps include: (1) reacting a hydrophilic chain oligomer, a hydrophobic chain oligomer, and a polydimethylsiloxane oligomer with diisocyanate to obtain a precursor; (2) reacting the precursor with a diselenide chain extender and a diol chain extender having a functional group A to obtain a chain extension intermediate; (3) The chain extension intermediate is mixed with a monomer having a functional group B and an epoxy group, and the functional group A reacts with the functional group B to obtain a post-crosslinkable amphiphilic polyurethane having an epoxy group and capable of controlling the release of nitric oxide.
4. The preparation method according to claim 3, characterized in that: The diol chain extender with functional group A and the monomer with functional group B and epoxy group are selected from one of the following combinations: Ⅰ: The diol chain extender with functional group A is selected from tertiary amine diol chain extenders or diol nitrogen heterocyclic chain extenders, and the monomer with functional group B and epoxy group is selected from monomers with halogen and epoxy group; II: The diol chain extender with functional group A is selected from diol chain extenders with halogen, and the monomer with functional group B and epoxy group is selected from monomers with tertiary amine and epoxy group; III: the diol chain extender with functional group A is selected from diol chain extenders with disulfide bonds, and the monomer with functional group B and epoxy group is selected from monomers with double bonds and epoxy groups; Preferably, the tertiary amine diol chain extender or diol nitrogen heterocyclic chain extender in combination I is selected from at least one of methyldiethanolamine, ethyldiethanolamine, and N,N-bis(2-hydroxyethyl)isonicotinamide, and the monomer with halogen and epoxy group is selected from at least one of epichlorohydrin, epibromohydrin, epifluorohydrin, (iodomethyl)oxirane, 3-iodooxetane, epichlorohydrin, 4-bromo-1,2-oxitane, 2-(chloromethyl)-1,2-oxitane, 3-bromooxitane, 3-ethyl-3-bromomethyloxitane, and 3-(bromomethyl)-2,2-dimethyloxitane; The halogen-containing diol chain extender in combination II is selected from at least one of 4-chloro-1,3-butanediol, 4-bromo-1,2-butanediol, dibromoneopentyl glycol, and 1,4-dichloro-2,3-butanediol, and the monomer with tertiary amine and epoxy group is selected from 1,2-epoxy-3-(diethylamino)propane 、 At least one of (oxiran-2-yl)methyl]dipropylamine, butyl(methyl)[(oxiran-2-yl)methyl]amine, N-methyl-N-[(oxiran-2-yl)methyl]cyclohexylamine, and bis(2-methylpropyl)[(oxiran-2-yl)methyl]amine; The diol chain extender with a disulfide bond in combination III is selected from at least one of trans-1,2-dithiane-4,5-diol and 3,6-dithia-1,8-octanediol; The monomer with double bonds and epoxy groups is selected from at least one of glycidyl methacrylate, allyl glycidyl ether, glycidyl acrylate, 2-vinyl oxirane, 2-(1-methylethylene)oxirane, 3,4-epoxy-1-butene, 1,2-epoxy-5-hexene, 1,2-epoxy-4-vinylcyclohexane, 1,2-epoxy-7-octene, and 1,2-epoxy-9-decene.
5. The preparation method according to claim 3, characterized in that: The structural formula of the diselenideol chain extender is shown in Formula VII: Among them, v=1~5.
6. The preparation method according to claim 3, characterized in that: The reaction temperature of step (1) is 50-60°C and the reaction time is 6-10h; The reaction temperature of step (2) is 50-60°C and the reaction time is 8-12h; The reaction temperature of step (3) is 50-60°C and the reaction time is 8-12h; Preferably, the reaction temperature of steps (1)-(3) is 55°C, the reaction time of step (1) is 8 hours, and the reaction time of steps (2) and (3) is 10 hours.
7. The preparation method according to claim 3, characterized in that: The polydimethylsiloxane oligomer is selected from at least one of bis-aminopropyl terminated polydimethylsiloxane and bis-hydroxy terminated polydimethylsiloxane; The hydrophilic chain oligomer is selected from at least one of polyethylene glycol, polyetheramine, propylene glycol-ethylene glycol copolymer, and zwitterionic compounds; The hydrophobic chain oligomer is selected from at least one of polycarbonate diol, polytetramethylene glycol, and polypropylene glycol; The diisocyanate is selected from at least one of diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate and hexamethylene diisocyanate; Preferably, the polydimethylsiloxane oligomer is bisaminopropyl terminated polydimethylsiloxane, the hydrophilic chain oligomer is polyetheramine, the hydrophobic chain oligomer is polycarbonate diol, and the diisocyanate is dicyclohexylmethane diisocyanate.
8. A polyurethane glucose limiting membrane, characterized in that The post-crosslinkable nitric oxide-controllable amphiphilic polyurethane for release is prepared by adding a crosslinking agent to the post-crosslinkable nitric oxide-controllable amphiphilic polyurethane for release according to claim 1 or 2 or the preparation method according to any one of claims 3 to 7.
9. The polyurethane glucose limiting membrane according to claim 8, characterized in that The cross-linking agent is selected from at least one of polyetheramine, polyethylene glycol diamine, and polytetrahydrofuran ether diamine; Preferably, the cross-linking agent is polyetheramine.
10. A working electrode for a glucose sensor, characterized in that: The working electrode is provided with the polyurethane glucose limiting membrane according to claim 8 or 9; Preferably, the thickness of the polyurethane glucose limiting membrane is 20-60 μm, preferably 30 μm; and / or An enzyme layer is also arranged between the working electrode and the polyurethane glucose limiting membrane, and the enzyme layer includes glucose oxidase; More preferably, the thickness of the enzyme layer is 1-10 μm, preferably 3 μm.
11. A glucose sensor, characterized in that: The glucose sensor comprises the working electrode according to claim 10.
Citation Information
Patent Citations
Selenium-containing polyurethane with stable and controllable release of nitric oxide, preparation method and application thereof
CN109651586A
Cited By
Amphiphilic polyurethane capable of being subjected to post-crosslinking, preparation method of amphiphilic polyurethane and application of amphiphilic polyurethane in glucose sensor
CN117603426A